Antimicrobial susceptibility patterns of clinically significant Gram-positive anaerobic bacteria in a Greek tertiary-care hospital, 2017–2019. (August 2020) - Maraki, Sofia; Mavromanolaki, Viktoria Eirini; Stafylaki, Dimitra; Kasimati, Anna
Abstract: Antimicrobial resistance among anaerobic bacteria is increasingly recognized with geographic differences. In this study we analyzed the distribution and antimicrobial susceptibility profiles of 358 Gram-positive clinically significant anaerobes, isolated from 2017 to 2019, in a Greek tertiary-care hospital. The species identification was performed by Vitek 2 and conventional biochemical methods, and the antimicrobial susceptibility testing by the E-test method. The antimicrobial agents tested were penicillin, ampicillin, amoxicillin-clavulanic acid, piperacillin-tazobactam, cefoxitin, imipenem, meropenem, clindamycin, metronidazole, moxifloxacin, chloramphenicol, tigecycline and vancomycin. Clostridioides difficile isolates were also tested against tetracycline. The results were interpreted using the CLSI and the EUCAST breakpoints. Clostridium species accounted for 35.5% of the isolates, followed by Gram-positive cocci (GPAC) (33.2%) and non-spore-forming bacilli (31.3%). Beta-lactams, β-lactam/β-lactamase inhibitors, cefoxitin, carbapenems, chloramphenicol, tigecycline and vancomycin proved all effective against the GPAC tested. Clindamycin, moxifloxacin and metronidazole resistance varied among different species of GPAC. Clindamycin and moxifloxacin resistance observed was 10% and 5% for Cutibacterium acnes, 25% and 6.2% for Actinomyces odontolyticus and 40% and 5% for Clostridium perfringens. C. difficile isolates were fully susceptible to metronidazole, vancomycin, and tigecycline. Resistance rates to clindamycin, moxifloxacin and tetracycline were 62.9%, 30% and 24.3%, respectively. These data highlight the need for periodic surveillance to monitor changes in susceptibility profiles. Highlights: Antimicrobial susceptibility patterns of Gram-positive anaerobes from Greece. Resistance to clindamycin, and moxifloxacin was high and varied among species. β-lactams, tigecycline and vancomycin had excellent activity against most species. C. difficile strains were susceptible to metronidazole, vancomycin and tigecycline.